A assistência social na constituição federal de 1988 - Barbosa, Dionísia Helena de Carliris Oliveira (2012)
This research seeks to decipher the historical and legal aspects that the institution of social assistance policy as a right to be through the state. For this, the effort to look in history for the movement of the formation of civil, political and social rights, allowed the identification of peculiar to the formation of these rights in Brazil. Such peculiarities are related to the Brazilian social and political formation and its patronizing and patronizing, which are still felt today in the slow process of search for full citizenship. The work highlights that, in the country, the logic of construction of the rights occurred in an inverted form, before being proclaimed the social rights, however, from the point of view of a government concession. Then came the political and and then civilians, which remain inaccessible to the large population. O The purpose of this historical effort is to demonstrate that rights are products of human sociability and, therefore, are formed according to political conditions, economic and cultural conditions of a certain period. Social assistance, for example, in the Brazil, only reached the category of law, in 1988, with the Citizen Constitution. Among the factors that led to this advance, is the emergence of the social and conflicts. Thus, it became necessary to think of policies that conflicts. Different types of social assistance have developed constitutional, always linked to charity and Benesse. The analysis of this trajectory shows that social assistance was not institutionalized due to the mere identification of social contingencies. She coat of a strong political content that guides its practice. Despite the status constitutional rights, as well as other Brazilian social rights, social assistance still struggle to fully consolidate itself as a right. The determinations economic conditions, however, become obstacles to its materialization.